2002
DOI: 10.1053/gast.2002.33661
|View full text |Cite
|
Sign up to set email alerts
|

Norwalk virus binds to histo-blood group antigens present on gastroduodenal epithelial cells of secretor individuals

Abstract: rNV VLPs use H type 1 and/or H types (3/4) as ligands on gastroduodenal epithelial cells of secretor individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
440
4
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 459 publications
(465 citation statements)
references
References 43 publications
18
440
4
3
Order By: Relevance
“…Consistent with this, HuNoVs can be internalized by enterocytes in culture [30][31][32] and MuNoVs can be transcytosed across a confluent epithelial monolayer to target underlying permissive macrophages 33 ; in all of these studies, no evidence of viral replication in the enterocytes themselves was noted. Indeed, we confirmed that the GII.4-Sydney HuNoV could cross a confluent intestinal epithelial monolayer to infect underlying B cells in the basal chamber of a transwell system.…”
Section: A Gii4-sydney Human Norovirus Infects B Cells In Vitromentioning
confidence: 72%
See 1 more Smart Citation
“…Consistent with this, HuNoVs can be internalized by enterocytes in culture [30][31][32] and MuNoVs can be transcytosed across a confluent epithelial monolayer to target underlying permissive macrophages 33 ; in all of these studies, no evidence of viral replication in the enterocytes themselves was noted. Indeed, we confirmed that the GII.4-Sydney HuNoV could cross a confluent intestinal epithelial monolayer to infect underlying B cells in the basal chamber of a transwell system.…”
Section: A Gii4-sydney Human Norovirus Infects B Cells In Vitromentioning
confidence: 72%
“…Because we used unprocessed stool as a source of virus, we reasoned that the most likely candidate for a filterable co-factor was commensal bacteria. In selecting a specific commensal bacteria to test for stimulatory activity, we were guided by the knowledge that HuNoVs bind HBGAs in a virus strainspecific manner 30,41 and that certain bacteria express glycans indistinguishable from human HBGAs. 42 In fact, Miura et al recently revealed that HBGAexpressing commensal bacteria such as Enterobacter cloacae can bind HuNoV VLPs.…”
Section: Commensal Bacteria Facilitate Norovirus Infectionsmentioning
confidence: 99%
“…In humans, genetic factors such as polymorphisms in the FUT1 (H), FUT2 (Se), and FUT3 (Le) genes that code for glycosyltransferases responsible for producing carbohydrate chains have been associated with susceptibility to NoV GI and II (23,26,27). At present we are evaluating reagents and assays to test for HBGA in pigs to ascertain if the same or similar genetic factors influence NoV infection of Gn pigs.…”
Section: Discussionmentioning
confidence: 99%
“…The third and last case we will consider here is autosomal recessive fucosyltransferase 2 (FUT2) deficiency, which was discovered in 2003. Individuals with this deficiency are naturally resistant to diarrhea caused by noroviruses (8,9). This condition is typically benign in the developed world today but would have been potentially lifethreatening in ancient times, as it still is in developing countries.…”
Section: Other Forms Of Mendelian Resistance To Infectionmentioning
confidence: 99%